2020
DOI: 10.1074/jbc.ra120.013869
|View full text |Cite
|
Sign up to set email alerts
|

The Cyt1Aa toxin from Bacillus thuringiensis inserts into target membranes via different mechanisms in insects, red blood cells, and lipid liposomes

Abstract: Bacillus thuringiensis subsp. israelensis produces crystal inclusions composed of three-domain Cry proteins and cytolytic Cyt toxins, which are toxic to different mosquito larvae. A key component is the Cyt toxin, which synergizes the activity of the other Cry toxins, thereby resulting in high toxicity. The precise mechanism of action of Cyt toxins is still debated, and two models have been proposed: the pore formation model and the detergent effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…It has been shown that the N-terminal region is responsible for the toxin oligomerization, and the C-terminal region is involved in the binding of the toxin to the membrane [ 84 ]. Specific amino acid residues and protein regions that affect Cyt1Aa binding, oligomerization, and membrane insertion have been investigated [ 75 , 85 , 86 , 87 ]. The second model is the detergent-like model, where it is proposed that the Cyt toxin aggregates nonspecifically on the cell membrane, leading to lipid bilayer disassembly and cell death [ 77 , 88 ].…”
Section: Toxins and Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the N-terminal region is responsible for the toxin oligomerization, and the C-terminal region is involved in the binding of the toxin to the membrane [ 84 ]. Specific amino acid residues and protein regions that affect Cyt1Aa binding, oligomerization, and membrane insertion have been investigated [ 75 , 85 , 86 , 87 ]. The second model is the detergent-like model, where it is proposed that the Cyt toxin aggregates nonspecifically on the cell membrane, leading to lipid bilayer disassembly and cell death [ 77 , 88 ].…”
Section: Toxins and Mode Of Actionmentioning
confidence: 99%
“…aegypti larvae but not for red blood cells [ 85 ]. Therefore, Cyt toxin insertion by the pore formation model could occur in microvilli membranes, while a detergent membrane interaction seems to be related to its hemolytic activity [ 87 ].…”
Section: Toxins and Mode Of Actionmentioning
confidence: 99%
“…Cyt1Aa acts by binding to specific receptors on the membrane of midgut epithelial cells ( 55 ). This binding triggers a conformational change in Cyt1Aa, allowing it to insert into the cell membrane and form pores or channels ( 56 , 57 ). These pores disrupt the integrity of the midgut membrane, leading to the leakage of cellular contents and loss of osmotic balance.…”
Section: Discussionmentioning
confidence: 99%
“…Thuringiensis has been found to have unique biological activities. Among them are cytotoxicity specific to certain human cancer cells (Mizuki et al, 2000;Aboul-Soud et al, 2019;Mendoza-Almanza et al, 2020), lectin activity against mammalian red blood cells (Torres-Quintero et al, 2018;Onofre et al, 2020), and activity against trichomonads (Lee et al, 2017). Future research will include tests of parasporal proteins, e.g., animal feces, which may affect indicators of biological activity unrelated to pathogenicity.…”
Section: Discussionmentioning
confidence: 99%